Maintenance of Muscle Mass and Cardiorespiratory Fitness to Cancer Patients During COVID-19 Era and After SARS-CoV-2 Vaccine - Conceição, Miguel S.; Derchain, Sophie; Vechin, Felipe Cassaro; Telles, Guilherme; Maginador, Guilherme Fiori; Sarian, Luís Otávio; Libardi, Cleiton Augusto; Ugrinowitsch, Carlos (Frontiers in Physiology, 2021)
There is emerging evidence that decreased muscle mass and cardiorespiratory fitness (CRF) are associated with increased risk of cancer-related mortality. This paper aimed to present recommendations to prescribe effective and safe exercise protocols to minimize losses, maintain or even improve muscle mass, strength, and CRF of the cancer patients who are undergoing or beyond treatment during the COVID-19 era. Overall, we recommend performing exercises with bodyweight, elastic bands, or suspension bands to voluntary interruption (i.e., interrupt the exercise set voluntarily, according to their perception of fatigue, before concentric muscular failure) to maintain or increase muscle strength and mass and CRF during COVID-19 physical distancing. Additionally, rest intervals between sets and exercises (i.e., long or short) should favor maintaining exercise intensities between 50-80% of maxHR and/or RPE of 12. In an exercise program with these characteristics, the progression of the stimulus must be carried out by increasing exercise complexity, number of sets, and weekly frequency. With feasible exercises attainable anywhere, modulating only the work-to-rest ratio and using voluntary interruption, it is possible to prescribe exercise for a wide range of patients with cancer as well as training goals. Exercise must be encouraged; however, exercise professionals must be aware of the patient's health condition even at a physical distance to provide a safe and efficient exercise program. Exercise professionals should adjust the exercise prescription throughout home confinement whenever necessary, keeping in mind that minimal exercise stimuli are beneficial to patients in poor physical condition.